Warthin’s Tumor: A Rare Case Report of a Bilateral Multifocal Parotid Tumor Associated with an Ectopic Tumor - Joana Silva; Nelson Teixeira; Nuno Ramos; Sância Ramos (Acta Médica Portuguesa)
Warthin’s tumor is the second most common benign neoplasm of the parotid gland and frequently presents with multifocal and bilateral involvement, either synchronously or metachronously, up to 20% - 30% of cases. More rarely, extraparotid locations may also occur. This case report describes a Warthin’s tumor presenting synchronously as a multifocal bilateral parotid tumor in association with an extraparotid localization, which, according to the existing literature, appears to be a rare event. This low incidence is likely underestimated and could be explained by several reasons. Increased awareness of this potentially higher incidence may aid physicians in better evaluating and treating their patients.